Fertilization, hatching and survival rates in heatshock induced Triploid purebred African Catfish, Clarias gariepinus (Burchell, 1822). - Sto. Domingo, Regina Kristine Arollado
The African catfish, Clarias gariepinus (Burchell, 1822) is one of the most suitable tropical ctfish species for aquaculture. It is considered to hold great promise for fish farming in Africa showing fast growth rate, large size and high resistance to handling and stress., This special problem was conducted to compare the performance of triploid Clarias gariepinus x Clarias gariepinus exposed to heatshock from the normal diploid individuals. More specifically, this study aimed to compare their fertilization, hatching and survival rates at day 2 and day 5 post-hatching. Heatshock treatments of the artificially fertilized eggs were done for 3.5 minutes duration at 35 degrees centigrade, 37 degrees centigrade and 39 degrees centigrade. Based on experimental results, the control group showed higher fertilization, hatching and survival rate values comapred to the experimental group.